Inhibiting retinoic acid signaling in dendritic cells suppresses respiratory syncytial virus infection through enhanced antiviral immunity - Farazuddin, Mohammad; Acker, Grant; Zourob, Joseph; O’Konek, Jessica J.; Wong, Pamela T.; Morris, Susan; Rasky, Andrew J.; Kim, Chang H.; Lukacs, Nicholas W.; Baker, James R. (iScience, 2024)
Retinoic acid (RA), controls the immunoregulatory functions of many immune cells, including dendritic cells (DCs), and is important for mucosal immunity. In DCs, RA regulates the expression of pattern recognition receptors and stimulates interferon production. Here, we investigated the role of RA in DCs in mounting immunity to respiratory syncytial virus (RSV). To abolish RA signaling in DCs, we used mice expressing a dominant negative form of retinoic acid receptor-α (RARα) under the CD11c promoter (CD11c-dnRARα). Paradoxically, upon RSV challenge, these animals had lower viral burden, reduced pathology, and greater Th1 polarized immunity than wild-type (WT) mice. Moreover, CD11c-dnRARα DCs infected with RSV showed enhancement in innate and adaptive immunity genes, while genes associated with viral replication were downregulated. These findings suggest that the absence of RA signaling in DCs enhances innate immunity against RSV infection leading to decreased viral load and reduced pathogenicity. [Display omitted] •RA signaling in DCs regulates their innate immunity against RSV•Loss of RA signaling in DCs suppresses RSV infection and reduces lung metaplasia•Blocking RA signaling in pDCs but not AMs increase their type I and III IFNs•Increased IFNs by pDCs and CD40 on cDCs enhances Th1 and suppresses Th2 to RSV infection Immunology; Virology; Cell biology.